Status of research and management of coastal saline soils for increasing crop productivity and future scope for improvement - SEN, H S; MAJI, B (The Indian Journal of Agricultural Sciences, 2013)
The review suggests improved management practices for the coastal saline soils. In the soilg showing poor water-transmission property, addition of amendments like and, rice husk or rice straw was found beneficial to improve leaching under limited water availability. Presence of subsurface drains also helped in increasing the leaching of salts in silty clay-loam soil. To increase nitrogen-use efficiency of waterlogged rice (Oryza sativa L), volatilization loss could be effectively checked through its placement at 5 cm soil depth. Slower mineralization of organic nitrogen in saline soil and inadequate use of fertilizer nitrogen ate the other reasons for poor nutrition of the crop. Availability of phosphorus depends on the pH and salinity of the soil, whereas potassium reserve in the soil is normally high, and therefore its application may be avoided in most of the soils. In view of the rising energy cost and limited input availability,. recycling of organic wastes and use of renewable sources of bio-fertilizers as an integrated nutrient- management package prove useful for sustained production. Since irrigation water is scarce, additional surface resource may be created by storing the excess rainwater in monsoon in the dug-out pond in one-fifth of the farmÂ holdings for multiple cropping. Underground water is under-utilized incoastalareas,and if properly utilized, along wilh surface sources, 43.86 million ha (forming 50% of the total cultivated area) may be brought under irrigation by 2010 AD. The coastal lands need protection against total inundation through protective embankments, designed suitably. preferably brick-pitched, with 1 m free board above the high-tide level. Planting of wind-breaks is useful in preventing wind erosion, particularly in areas baving sand dunes. Excess rainwater in monsoon should be channelized through primary and secondazy drains and let out through one-way sluice gate, designed to meet the drainage coefficient of the catchment. The existing low cropping intensity wirh generally only 1 crop of rainfed rice should be improved through multi-tier cropping systems, involving arable, horticultural. plantation and forest species along with improved soil, fertilizer and Water management for greater land use and increased productivity.